The Practices of The Government In The Provision of Intolerance Between Religions and The Response of Society In The Cabpaten - Setiawan, Juliandi; Warnisyah Harahap, Elly; Harahap, Salahuddin (Dinasti Research, 2024)
This study examines government policies to prevent intolerant behavior among religious communities and the response of the community in Aceh Tanggara district. This study aims to identify policies that have been implemented by the local government and evaluate their effectiveness in preventing intolerant behavior. The research method used is qualitative with a case study approach. Data was collected through in-depth interviews, participatory observation, and analysis of official documents. The results show that the government has adopted various policies, such as interfaith dialogue programs, multicultural education in schools, and inclusive religious social activities. Nonetheless, community responses show variations, ranging from full support to resistance. Factors influencing community responses include level of education, religious understanding and personal experience of religious harmony. The study concludes that although government policies are quite comprehensive, their successful implementation relies heavily on active participation and community awareness.